Środki ochrony prawnej w zamówieniach publicznych a konstytucyjna zasada prawa do sądu - Kuderczak, Przemysław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Public procurements are an economic area, in which widely understood public sector is buying goods and services by spending public funds according to specific rules and legal norms. But, by creating a public procurement legislation, has legislature provided the constitutional principle of access to justice?
Keywords: constitution; right to court; public orders; economic turnoverl; appeal